Adapting Regional Clusters to Globalization and Crisis: The Role of Internal and External Linkages in Cluster Evolution, with a Focus on Tourism Clusters - Marek SZTURO; Krzysztof GRABOWSKI (Communications of International Proceedings, 2023)
In response to crisis threats and the challenges of globalization and informatization, processes oriented toward a system of internal or external linkages are taking place in regional industry clusters (clusters). Strategies directed at networks of connections within the region do not protect against the threat of isolation, which implies negative externalities of the network and the danger of crisis. Strategies based on the construction of foreign ties, associated with the relocation of selected elements of the value chain (so-called selective relocation), allow avoiding isolation and reaping positive network effects. The purpose of this article is to present the processes occurring in clusters, including tourism clusters, in light of the cluster evolution model. The model can be used to determine the phase of cluster development in a given regional environment, the impact of this phase on the development of the region and local businesses, and to determine the processes of evolution. The text is based on literature studies and empirical research in the field of cluster concepts.
Keywords: tourism; cluster; crisis